The Role of Work Motivation In Mediating the Effect of Workload and Work Culture on Employee Performance at the Uptd Of the Kerthi Bali Sadhajiwa Health Laboratory Center, Bali Province Health Office - Sri Indriani, Ida Ayu; Nengah Landra; Putu Kepramareni (International Journal of Economics (IJEC), 2025)
This study explores the role of work motivation as a mediating factor between workload and work culture on employee performance at the UPTD Kerthi Bali Sadhajiwa Health Laboratory Center. With a population of 113 employees, a quantitative approach was employed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) method for data analysis. The findings indicate that both workload and work culture significantly influence work motivation and employee performance. Specifically, while workload directly impacts employee performance, it does not significantly mediate through work motivation. In contrast, work culture positively influences both work motivation and employee performance, demonstrating partial mediation. The results emphasize the importance of a supportive work environment and effective workload management to enhance employee performance. Recommendations for management include fostering a positive work culture and developing motivational strategies to sustain employee engagement and productivity